Pengaruh Mahasiswa Magang terhadap Keberlangsungan Kinerja Kantor Walikota Medan - Muhammad Rifqi Akbar; Nurhayati Nurhayati (Universitas Muhammadiyah Enrekang, 2022)
Internship is a program held by each campus and is intended for every final semester student as a requirement to complete final education, it is hoped that students will gain experience and explore their potential before entering the world of work. This study aims to determine the effect of student interns on the performance of Medan Mayor's Office employees. And therefore this internship activity should be able to provide benefits for both parties, both from interns who are given the opportunity to study, and from employees whose workloads are eased because of the assistance provided by the interns. But in reality it is different, as said by one of the employees in one of the government agencies in Medan City. And the result of this discussion is that the employees tend to give a positive response to the existence of interns.